PANDEMI COVID-19 & MAKNA SOSIAL - Bambang Amir Alhakim; Ishomuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2022)
Abstract: This study aims to understand the social meaning of some community members for the occurrence of the covid-19 outbreak (pandemic). The method used to reveal the social meaning is descriptive qualitative. In practice, the writers use Max Weber's theory of social action based on